YEREL EDEBİYAT DERGİLERİNE BİR ÖRNEK; TARANCI DERGİSİ - Kardaş, Canser (Dicle Üniversitesi, 2012)
Türk edebiyatında dergiciliğin edebiyata ve edebiyat tarihine katkılarını ortaya çıkarmak için yayımlanmış dergilerin incelenmesi büyük önem arz etmektedir. Bu amaçla kaleme alınan yazımız, II. dönem açılan Diyarbakır Halkevinin yayın organı olan “Tarancı” dergisi incelenmiştir. 29 Nisan 1910 yılında yayımlanan “Kevkeb Medinho” [Şark Yıldızı] dergisiyle Diyarbakır’da uzun soluklu bir dergicilik faaliyeti başlamıştır. 1910-2011 yılları arasında 50’yi aşkın dergi yayımlanmıştır. Dergi hem sayısal analizlerle hem de muhteva yönünden ortaya konmaya çalışılmıştır

The Investigetion of the published journals is very important to exposing the contribution of the magazine publishing to the literature and history of literature in Türkish literature. In our paper, written to this end, is the Journal Tarancı, the publication of the Diyarbakır Public House, which oppened II. Session, isvestigated. With the “Kevkeb Medinho” [Şark Yıldızı or The Star of East], published on 29 April 1910, started a long- term magazin publishing activity in Diyarbakır. Between the years 1910 and 2011 has been published more than 50 different journals. It has been tried to present the Journal, both with numerical analysis and in terms of content
An Example For The Regional Literary Magazines: Journal Tarancı